On the Rainbow Connection Number for Snowflake Graph - Lyra Yulianti; Muhammad Rafif Fajri; Des Welyyanti; Aisyah Nurinsani (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Let G be an arbitrary non-trivial connected graph. An edge-colored graph G is called a rainbow connected if any two vertices are connected by a path whose edges have distinct colors, such path is called a rainbow path. The smallest number of colors required to make G rainbow connected is called the rainbow connection number of G, denoted by rc(G). A snowflake graph is a graph obtained by resembling one of the snowflake shapes into vertices and edges so that it forms a simple graph. Let be a generalized snowflake graph, i.e., a graph with paths of the stem, pair of outer leaves, middle circles, and pairs of inner leaves. In this paper we determine the rainbow connection number for generalized snowflake graph .